Interview with Gerald Vizenor - Vizenor, Gerald; Chambers, Clarke A. (University of Minnesota, 1996)
Clarke A. Chambers interviews Gerald Vizenor, professor for the Department of American Indian Studies.
Keywords: Vizenor, Gerald; Chambers, Clarke A.; Department of American Indian Studies; General College